2020
DOI: 10.1016/j.immuni.2020.04.002
|View full text |Cite
|
Sign up to set email alerts
|

FADD and Caspase-8 Regulate Gut Homeostasis and Inflammation by Controlling MLKL- and GSDMD-Mediated Death of Intestinal Epithelial Cells

Abstract: Pathways controlling intestinal epithelial cell (IEC) death regulate gut immune homeostasis and contribute to the pathogenesis of inflammatory bowel diseases. Here, we show that caspase-8 and its adapter FADD act in IECs to regulate intestinal inflammation downstream of Z-DNA binding protein 1 (ZBP1)-and tumor necrosis factor receptor-1 (TNFR1)-mediated receptor interacting protein kinase 1 (RIPK1) and RIPK3 signaling. Mice with IEC-specific FADD or caspase-8 deficiency developed colitis dependent on mixed lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
185
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(190 citation statements)
references
References 53 publications
(67 reference statements)
5
185
0
Order By: Relevance
“…Caspase-8 is a master regulator of several cell death pathways, including apoptosis, necroptosis, and pyroptosis. 19 Its role in regulation of inflammatory responses has been recently reported in the context of fungal infection. We found that SARS-CoV-2 induces caspase-8 activation to trigger cell apoptosis and to directly process inflammatory factors such as pro-IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-8 is a master regulator of several cell death pathways, including apoptosis, necroptosis, and pyroptosis. 19 Its role in regulation of inflammatory responses has been recently reported in the context of fungal infection. We found that SARS-CoV-2 induces caspase-8 activation to trigger cell apoptosis and to directly process inflammatory factors such as pro-IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that pathways of cell death are associated in different ways according to the activation of signaling cascades inducing apoptosis, necroptosis, and pyroptosis 24 . An increasing body of evidence suggests that receptor interacting protein kinase 1 and caspase-8 are the mediators of the cross-talk between apoptosis, necroptosis, and pyroptosis and determine the type of cell death induced in response to activation of cell death signaling 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The comparative study of the distribution of selected pyroptosis and apoptosis markers in the striatum showed that young mice, both wild type and R6/2, express high levels of the cleavage product of Caspase-8. We associate this phenomenon to the physiological process of cell homeostasis 25 , 27 . This was also confirmed by the lack of immunoreactivity for cleaved Caspase-8 in the 13-week-old mice, both wild type and R6/2.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammasome-driven lytic cell death is, therefore, lost in Canidae and this is particularly interesting because the Carnivora also lack the necroptotic effector MLKL such that two of the critical inflammatory cell death pathways that are thought to be essential for host protection against infection are absent. One of the key functions for inflammatory cell death is to protect the gut against infection (Crowley et al, 2020; Rauch et al, 2017; Schwarzer et al, 2020; Sellin et al, 2014; Tummers et al, 2020) yet canonical inflammasome, non-canonical inflammasome and necroptotic lytic cell death pathways in Carnivora are inactive. Emerging ecological evidence suggests that a high protein diet, such as that consumed by the Carnivora, is antimicrobial (Cotter et al, 2019) and we speculate that the evolutionary and functional reduction in inflammasome activation in the Carnivora may simply reflect the protection against infection conferred on these animals by their dietary habits.…”
Section: Discussionmentioning
confidence: 99%